A pilot randomized placebo-controlled study on modified MaZiRenWan: a formulated Chinese medicine to relieve constipation for palliative cancer patients - Chung-wah Cheng; Hoi-fung Mok; Cora W. S. Yau; Jasmine T. M. Chan; Yu-chen Kang; Pui-yan Lam; Linda L. D. Zhong; Chen Zhao; Bacon F. L. Ng; Annie O. L. Kwok; Doris M. W. Tse; Zhao-xiang Bian (BMC, 2022)
Abstract Background Constipation is a common problem among advanced cancer patients; however, many of them find limited effective from current therapies. Thus, we aimed to test the effect of a traditional Chinese herbal formula, modified MaZiRenWan (MZRW), by comparing with placebo among palliative cancer patients with constipation. Methods This is a randomized, double-blind, placebo-controlled trial. Participants aged over 18 were recruited and randomized to MZRW or placebo group in addition to current prescriptions (including ongoing laxatives treatment) for two weeks. Exclusion criteria included cognitive impairment, presence of a colostomy or gastrointestinal obstruction and estimated life expectancy of less than one month. Individualized modification of MZRW was allowed according to the traditional Chinese medicine (TCM) pattern of patient. The primary outcome was the global assessment of improvement, which reflected whether the constipation had improved, remained the same or worsened. Results Sixty patients, with mean age 75.2 years (range 47-95 years), were randomized to MZRW or placebo group. Among the MZRW group, 59.3% (16/27) had improvement in the global assessment score, as compared with 28.6% (8/28) of the placebo group (p-value = 0.022). Besides, the MZRW group had significant increase in stool frequency, and reduction in constipation severity and straining of defecation (p-value < 0.05). No serious adverse event was reported due to the research medication. Conclusion This pilot trial suggests modified MZRW is well-tolerated and effective for relief of constipation in patients with advance cancer. It could be considered as a potential treatment option for constipation in palliative care. Trial registration: The trial had been registered in ClinicalTrials.gov with identifier number NCT02795390 [ https://clinicaltrials.gov/ct2/show/NCT02795390 ] on June 10, 2016.